Characterization and structure-property relationships of an injectable thiol-Michael addition hydrogel toward compatibility with glioblastoma therapy. (May 2022) - Khan, Zerin Mahzabin; Wilts, Emily; Vlaisavljevich, Eli; Long, Timothy E.; Verbridge, Scott S.
Abstract: Glioblastoma multiforme (GBM) is an aggressive primary brain cancer and although patients undergo surgery and chemoradiotherapy, residual cancer cells still migrate to healthy brain tissue and lead to tumor relapse after treatment. New therapeutic strategies are therefore urgently needed to better mitigate this tumor recurrence. To address this need, we envision after surgical removal of the tumor, implantable biomaterials in the resection cavity can treat or collect residual GBM cells for their subsequent eradication. To this end, we systematically characterized a poly(ethylene glycol)-based injectable hydrogel crosslinked via a thiol-Michael addition reaction by tuning its hydration level and aqueous NaHCO3 concentration. The physical and chemical properties of the different formulations were investigated by assessing the strength and stability of the polymer networks and their swelling behavior. The hydrogel biocompatibility was assessed by performing in vitro cytotoxicity assays, immunoassays, and immunocytochemistry to monitor the reactivity of astrocytes cultured on the hydrogel surface over time. These characterization studies revealed key structure-property relationships. Furthermore, the results indicated hydrogels synthesized with 0.175 M NaHCO3 and 50 wt% water content swelled the least, possessed a storage modulus that can withstand high intracranial pressures while avoiding a mechanical mismatch, had a sufficiently crosslinked polymer network, and did not degrade rapidly. This formulation was not cytotoxic to astrocytes and produced minimal immunogenic responses in vitro . These properties suggest this hydrogel formulation is the most optimal for implantation in the resection cavity and compatible toward GBM therapy. Statement of significance: Survival times for glioblastoma patients have not improved significantly over the last several decades, as cancer cells remain after conventional therapies and form secondary tumors. We characterized a biodegradable, injectable hydrogel to reveal structure-property relationships that can be tuned to conform the hydrogel toward glioblastoma therapy. Nine formulations were systematically characterized to optimize the hydrogel based on physical, chemical, and biological compatibility with the glioblastoma microenvironment. This hydrogel can potentially be used for adjuvant therapy to glioblastoma treatment, such as by providing a source of molecular release for therapeutic agents, which will be investigated in future work. The optimized formulation will be developed further to capture and eradicate glioblastoma cells with chemical and physical stimuli in future research. Graphical abstract: Image, graphical abstract